From mice to men – mouse models in obesity research: What can we learn? - Scroyen, Ilse; Hemmeryckx, Bianca; Lijnen, H. Roger (Thrombosis and Haemostasis, 2013)
Obesity has become a world-wide epidemic and is associated with diseases such as diabetes, dyslipidaemia, cardiovascular disease and certain types of cancers. Understanding the adipose tissue developmental process, involving adipogenesis, angiogenesis and extracellular matrix remodelling, is therefore crucial to reveal the pathobiology of obesity. Experimental mouse models are extensively used to gain new insights into these processes and to evaluate the role of new key players, in particular proteolytic system components, in adipose tissue development and obesity. In this paper, we will review available in vitro and in vivo murine models of obesity and discuss their value in understanding the mechanisms contributing to obesity.
Keywords: Animal models; obesity; transgenic animals